1984
DOI: 10.1016/0014-5793(84)80297-5
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of beef heart mitochondrial F1‐ATPase by the 2′,3′‐dialdehyde derivatives of adenine nucleotides

Abstract: Beef fietzrf mitochondri~~ Ft-ATPase was i~~~t~vat~ by the 2" ,3 '-dialdehyde derivatives of ATP, ADP and AMP {ATP, oADP, oAMP). In the absence of Mg2+, i~a~t~~~on resuIWl from the binding Of 1 mol nuekotide analog per active unit of Fi. The most efficient andog was oADP, followed by oAMP and oATP, Complete inactivsxtion was correlated with the binding; of about 11 moi ["%]oADPr'mol Ft, After ~orr~~ti~r~ for non-specifk labeling, the ~~~~ber of sp~ifi~~~ly bound fi4C]oADP was 2-3 mol per mol Fi. By S~S-polyacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“… 12 An independent study showed that oxidized ATP also binds irreversibly to both α and β subunits of mitochondrial F 1 ATPase and decreases its activity. 13 Here we show that after internalization, LF localizes to mitochondria and interacts with F 1 F 0 complex proteins including, subunits β and γ, resulting in increased ATPase activity and depletion of cellular ATP, which is a critical early event in LT-induced sudden (pyroptotic) cell death.…”
Section: Introductionmentioning
confidence: 76%
“… 12 An independent study showed that oxidized ATP also binds irreversibly to both α and β subunits of mitochondrial F 1 ATPase and decreases its activity. 13 Here we show that after internalization, LF localizes to mitochondria and interacts with F 1 F 0 complex proteins including, subunits β and γ, resulting in increased ATPase activity and depletion of cellular ATP, which is a critical early event in LT-induced sudden (pyroptotic) cell death.…”
Section: Introductionmentioning
confidence: 76%